NEUROCOGNITIVE STATUS IN INDONESIAN HIV-INFECTED REPRODUCTIVE WOMEN - Lumbanraja, Sarma Nursani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Introduction: HIV-associated neurocognitive disorder (HAND) was emerging with the deficits inclusion of psychomotor, memory, attention, and verbal fluency. This situation could increase the burden of an HIV-positive subject in daily activities, either the economic or social burden. However, the cases were more likely isolated without exact prevalence data. Objective: This study aims to find the prevalence of HIV-HAND in Indonesia. Methods: This was an analytical research with cross-sectional design to assess neurocognitive status in reproductive age mothers who took regular ARVs for more than 6 months. Neurocognitive impairment in AIDS is diagnosed with the International HIV dementia scale. Data were analyzed using SPSS 19.0 Results: In this study, no subjects were diagnosed with had neurocognitive impairment. Only 1 of 29 subjects (3.4%) with CD4>350/mm3 had slight psychomotor disorders. Conclusion: This study showed that no subject with HIV infection in had dementia or neurocognitive impairment.